2014
DOI: 10.1159/000362367
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Toxoplasma gondii-</i></b>Derived Profilin Triggers Human Toll-Like Receptor 5-Dependent Cytokine Production

Abstract: Up to a third of the world's population is infected with Toxoplasma gondii. Natural infection in humans can be life threatening during pregnancy and in immunocompromised individuals. Toll-like receptor (TLR) 11 is the mouse innate sensor that recognizes T. gondii profilin; however, in humans the TLR11 gene leads to transcription of no functional protein. Herein, by using a multiple sequence alignment phylogenetic analysis program between human and mouse species, we found that human TLR5 seems to be the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…These findings are inconsistent with a recent report by Salazar Gonzalez et al . (28) who showed that TgPRF stimulates human monocytes to secrete IL-6 and IL-12 in a TLR5-dependent manner. The basis of this discrepancy is unclear but we speculate that it may stem from monocyte purification techniques employed by these authors which differ from those used here.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are inconsistent with a recent report by Salazar Gonzalez et al . (28) who showed that TgPRF stimulates human monocytes to secrete IL-6 and IL-12 in a TLR5-dependent manner. The basis of this discrepancy is unclear but we speculate that it may stem from monocyte purification techniques employed by these authors which differ from those used here.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of TLR5 occurs in intestinal epithelial cells, mainly at the basolateral surface; it recognizes invading flagellated pathogenic bacteria by identifying a protein called flagellin [33]. The amino acid sequence of TLR5 appears to be similar to those of TLR11 and TLR12 [115]; the latter two TLRs form a complex and recognize profilin-like proteins in Toxoplasma gondii (protozoan parasite) [108]. Finally, TLR10 may sense ligands derived from within the host rather than from microbes [102].…”
Section: Tlr Ligandsmentioning
confidence: 99%
“…Moreover, we observed that direct parasite-host cell contact is critical for TNF and IL-12 induction. 42 These findings are at odds with a recent study by Salazar Gonzalez et al , 43 who showed that T. gondii profilin stimulates human monocytes to secrete IL-6 and IL-12 in a TLR5-dependent manner. The basis of this discrepancy is unclear but may relate to the purity of the profilin or cell populations employed by the two laboratories.…”
Section: The Response Of Human Myeloid Cells To T Gondii Requires Phmentioning
confidence: 86%